2012
DOI: 10.1111/j.1365-2966.2012.20825.x
|View full text |Cite
|
Sign up to set email alerts
|

The peak energy of dissipative gamma-ray burst photospheres

Abstract: The radiation released at the transparency radius of an ultrarelativistic flow can account for the observed properties of gamma‐ray bursts (GRBs) provided that sufficient energy is dissipated in the sub‐photospheric region. Here, I investigate how the peak energy of the Ef(E) spectrum and its overall shape depend on the properties of the jet for various ‘dissipative photospheres’. I find that continuous energy release which results in electron heating over a wide range of distances may be the key to explain th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
118
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(124 citation statements)
references
References 49 publications
5
118
1
Order By: Relevance
“…If it is a consequence of the dominant radiation mechanism at work in GRBs, as we expect, theoretical studies may help understanding the nature and the true location of this boundary (see for instance Eichler & Levinson 2004;Yamazaki et al 2004;Rees & Mészáros 2005;Thompson et al 2007;Giannios 2012;Mochkovitch et al 2012;Beniamini & Piran 2013;Shahmoradi 2013, for explanations within the framework of different theoretical or phenomelogical models). The observation of an E pi -E iso relation in time-resolved spectra (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…If it is a consequence of the dominant radiation mechanism at work in GRBs, as we expect, theoretical studies may help understanding the nature and the true location of this boundary (see for instance Eichler & Levinson 2004;Yamazaki et al 2004;Rees & Mészáros 2005;Thompson et al 2007;Giannios 2012;Mochkovitch et al 2012;Beniamini & Piran 2013;Shahmoradi 2013, for explanations within the framework of different theoretical or phenomelogical models). The observation of an E pi -E iso relation in time-resolved spectra (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…In these models, the prompt emission is produced above the photosphere as suggested by the nonthermal spectrum. However, it has been shown that nonthermal emission can also be produced at the photosphere if a subphotospheric dissipation mechanism is at work Pe'er et al 2005;Ryde et al 2011;Giannios 2012;Beloborodov 2013). After the prompt phase, the afterglow is produced at larger distances and is due to the interaction of the jet with the ambient medium, which creates a strong external shock.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, several types of dissipation processes have been proposed: i) the so-called internal shock (IS) model (Rees & Meszaros 1994;Narayan et al 1992), in which the kinetic energy of a baryon load is dissipated into gamma rays through shocks that take place far away from the Thomson photosphere, at 10 14 -10 16 cm; ii) the photospheric models, in which the dissipation occurs near the photosphere, and where a Planckian spectrum is modified by some heating and Compton scattering (Rees & Mészáros 2005;Pe'er et al 2006; Thompson et al 2007;Derishev et al 1999;Rossi et al 2006;Beloborodov 2010;Titarchuk et al 2012;Giannios 2008;Mészáros & Rees 2011;Giannios 2012); iii) magnetised ejecta Full Tables 1−4 are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/589/A98 (σ = B 2 /4πΓρc 2 > 1) dissipate their energy at distances similar to those of IS (Lyutikov & Blandford 2003;Zhang & Yan 2011;Beniamini & Granot 2015).…”
Section: Introductionmentioning
confidence: 99%